Derivasi Solvabilitas Bank Mega Syariah: Analisis Longitudinal Rasio DER 2020–2024 - Nikmah, RA Ulfatun; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study focuses on how Bank Mega Syariah's solvency evolved from 2020 to 2024 through a longitudinal analysis of the Debt-to-Equity Ratio (DER). DER was chosen because it directly indicates how the bank balances the use of external funds with its equity, allowing changes in its figures to reflect the direction of its capital policy and its response to economic dynamics over the past five years. Using a quantitative descriptive approach based on annual financial report data, this study attempts to analyze patterns, not just numbers, to determine whether the bank's capital structure is moving toward stability or facing certain pressures. The results indicate that DER fluctuations during this period are not simply annual variations, but part of the bank's efforts to maintain a healthy capital position while still supporting financing activities. These findings demonstrate that consistent DER management is a crucial foundation for sustainable operations and stakeholder trust. However, this study recognizes its limitations in using only one solvency indicator. Therefore, further studies involving other ratios such as the Capital Adequacy Ratio (CAR) or the Financing-to-Deposit Ratio (FDR) would help provide a more comprehensive picture of the capital condition of Islamic banks.